Identification and delineation of potential castor growing areas in different Agro-eco sub regions of India: IDENTIFICATION AND DELINEATION OF CASTOR GROWING AREAS IN AGRO-ECO SUB REGIONS - L G K NAIDU,; S DHARUMARAJAN,; M LALITHA,; R VASUNDHARA,; V RAMAMURTHY,; G P OBI REDDY,; R S SINGH,; B TAILOR,; RAMESHWAR SINGH,; U BARUAH,; M PADMAIAH,; G SURESH,; et al. (Journal of Oilseeds Research, 2015)
Castor (Ricinus communis L.) is one of the oldest cultivated crops in the world. Castor oil is having global importance specially in chemical industry because it is the only commercial source of a hydroxylated fatty acid. Castor also hastremendousfuture potential as an industrial oilseed crop because of its high seed oil content, unique fatty acid composition, potentially high oil yields, and ability to be grown under drought and saline conditions. Soils and prevailing climatic conditions across different Agro-Eco Sub Regions (AESR) of India were assessed and matched with crop requirement criteria to identify the potential castor growing areas. Potential castor growing areas comprise favourable soil depth (deep soils) with longer Length of Growing Period (LGP). Among the traditional castor growing areas, AESR 5.2, 7.3, 8.2 and 8.3 have potential to grow castor whereas in non-traditional castor growing areas, AESR6.3, 6.2, 13.1, 15.4 and 17.1 are most potential for expanding castor cultivation. Relative yield and spread index of castor indicated that most of the potential areasidentified in different AESRsfall in zone II and III, need special attention to increase productivity and area expansion programme. Site specific management strategies like selection of suitable variety matching with LGP and proper adoption of nutrient management will overcome the limitations observed in these zones.